Taking a Chance on Workers: Evidence on the Effects and Mechanisms of Subsidized Employment from an RCT - Tania Barham; Brian C. Cadena; Patrick S. Turner (Institute of Labor Economics (IZA), 2023)
This paper estimates experimental impacts of a supported work program on employment, earnings, benefit receipt, and other outcomes. Case managers addressed employment barriers and provided targeted financial assistance while participants were eligible for 30 weeks of subsidized employment. Program access increased employment rates by 21 percent and earnings by 30 percent while participants were receiving services. Though gains attenuated after services stopped, treatment group members experienced lasting improvements in employment stability, job quality, and well-being, and we estimate the program's marginal value of public funds to be 0.64. Post-program impacts are entirely concentrated among participants whose subsidized job was followed by unsubsidized employment with their host-site employer. This decomposition result suggests that encouraging employer learning about potential match quality is the key mechanism underlying the program's impact, and additional descriptive evidence supports this interpretation. Machine learning methods reveal little treatment effect heterogeneity in a broad sample of job seekers using a rich set of baseline characteristics from a detailed application survey. We conclude that subsidized employment programs with a focus on creating permanent job matches can be beneficial to a wide variety of unemployed workers in the low-wage labor market.
Keywords: J24; J68; I38; H43; 330; subsidized employment; active labor market programs; randomized controlled trial